Signs of a Catastrophe: Predicted Shortage of Teachers of Lower Secondary Science and Technics and Technology in Slovenia - Dolenc, Kosta; Šorgo, Andrej; Ploj Virtič, Mateja (Revija za elementarno izobraževanje, 2021)
The paper provides evidence as a baseline for action to prevent the educational catastrophe that would result from the predicted shortage of STEM teachers in lower secondary schools in Slovenia. Based on the data, obtained from the relevant institutions, we can predict that, without a change in educational policy towards encouraging students to choose the teaching of STEM subjects as a career, the number of STEM teachers will fall below all acceptable levels.
Keywords: STEM teacher shortage; lower secondary schools; the economics of education